Pomen učiteljevih pojmovanj in prepričanj za profesionalni razvoj učiteljev - Ivajnšič, Anja; Ivanuš Grmek, Milena (Revija za elementarno izobraževanje, 2009)
The importance of teachers’ conceptions and convictions as they apply to the professional development of teachers. The article deals with teacher’s conceptions and convictions about their professional development. The first part of the article clarifies what is meant by the professional development of teachers and introduces important factors involved in the professional development of a teacher - teacher’s conceptions and convictions. The second part concerns the results of our research, which was based on the conceptions teachers have about group teaching and their tolerance toward uncertainty. We were interested in the difference between the teachers who have degrees in pedagogy from the former 2-year system and those who have university degrees in pedagogy from the modern 4-year system. We were also interested in the differences between the teachers’ conceptions based on the amount of teaching experience they have. There were statistically important differences between the teachers with degrees in pedagogy from the former 2-year system and those with modern 4-year university degrees in pedagogy. There were also statistically important differences between the teachers concerning the amount of teaching experience they had, which was confirmed in the case of four statements.